Solid State Damper Based on Foam Aluminum to Reduce Vibration Activity of Electromechanical Devices; Recent Developments in the Field of Non-Destructive Testing, Safety and Materials Science; Vol. 433 : Studies in Systems, Decision and Control (SSDC) - Ermakov D. V. Dmitry Vladimirovich (2023, 2023)
Title screen